OP0106 Effect of a Model Consultation on Quality of Care of Osteoarthritis: A Primary Care Cluster Randomised Trial. (9th June 2015) - Edwards, J.J.; Jordan, K.P.; Porcheret, M.; Healey, E.L.; Jinks, C.; Bedson, J.; Clarkson, K.; Hay, E.M.; Dziedzic, K.S.
Abstract : Background: Uptake of recommended assessment and management strategies for osteoarthritis (OA) in primary care has not consistently been achieved. Objectives: To determine the effect of a model OA consultation, informed by NICE OA recommendations, to support self-management of peripheral joint pain in adults aged ≥45 years on recorded quality of primary care. Methods: A two arm cluster-randomised unblinded controlled trial (registration: ISRCTN06984617 ) [1] used an electronic template [2] to record quality indicators of OA care. This was installed in 8 general practices 6 months (baseline period) before randomisation into intervention (n=4) or usual care (n=4) arms. In intervention practices, GPs and practice nurses received training on core NICE recommendations for OA (diagnosis, written information, exercise & physical activity, healthy eating, pain management) and in a model OA consultation. Patients in those practices received a consultation with the GP for joint pain, an OA guidebook, and up to 4 follow-up consultations with a practice nurse to support self-management. All practices continued with template use. Multilevel logistic regression (patients nested within clinician seen) analysis was performed on all patients aged ≥45 years consulting for OA in a 6 month period post randomisation. Outcomes were i) quality indicators of OA care, ii) routinely recorded management. Results: There were 1118 patients in the intervention arm, and 842 patients in the control arm. There was wide variation between practices and clinicians in achieved quality of care prior to randomisation. Uptake of written information on OA increased in intervention practices from 4% at baseline to 28%; written exercise advice from 4% to 22%; and written weight loss advice from 1% to 15%; but remained stable in control practices at 1-3%. At 6 months, patients in the intervention arm were more likely to have received paracetamol (odds ratio 1.74; 95% CI 1.27, 2.38), and physiotherapy referral (5.30; 95% CI 2.11, 13.34) but less likely to have had an x-ray (0.45; 95% CI 0.12, 1.72). There were no differences in any other routinely recorded management. Conclusions: The model OA consultation was associated with improvements in recorded quality indicators of OA care for core NICE recommendations. There remains a need to understand and reduce variability between practices and clinicians in primary care management of OA. References: Dziedzic KS, Healey EL, Porcheret M, Ong B, Main CJ, Jordan KP, et al. Implementing the NICE osteoarthritis guidelines: a mixed methods study and cluster randomised trial of a model osteoarthritis consultation in primary care - the Management of OsteoArthritis In Consultations (MOSAICS) study protocol. Implement Sci 2014;9(1):95 doi: 10.1186/s13012-014-0095-y Edwards JJ, Jordan KP, Peat G, Bedson J, Croft PR, Hay EM, et al. Quality of care for OA: the effect of a point-of-care consultation recording template. Rheumatology 2014 doi: 10.1093/rheumatology/keu411 Acknowledgements: This research was funded by a National Institute for Health Research (NIHR) Programme Grant (RP-PG-0407-10386) and is supported by the NIHR Collaborations for Leadership in Applied Health Research and Care West Midlands. The views expressed in this paper are those of the authors and not necessarily those of the NHS, the NIHR or the Department of Health. Disclosure of Interest: J. Edwards Employee of: Provider of general practice services and benefits financially from the Quality & Outcomes Framework, Speakers bureau: Invited speaker, EULAR 2015, K. Jordan: None declared, M. Porcheret: None declared, E. Healey: None declared, C. Jinks: None declared, J. Bedson Employee of: Provider of general practice services and benefits financially from the Quality & Outcomes Framework, K. Clarkson: None declared, E. Hay: None declared, K. Dziedzic: None declared